Posible ampliación de la CAN: algunos escenarios - Fairlie Reinoso, Alan Carsol Bernabe (El Colegio de México A.C., 2025)
Over its 55-year history, the Andean Community (can) has experienced periods of both growth and crisis. This article examines the possibilities and challenges of reintegrating Chile and Venezuela into the organization, as proposed in the XXII Declaration of the Andean Presidential Council in 2022. The study employs a conceptual approach and a qualitative methodology that combines critical analysis of secondary sources with semi-structured interviews with key stakeholders to assess the benefits of integration. It further explores trade flows and key exchange indicators among member countries, the can’s recent commercial and non-commercial agenda, and potential points of convergence with the policies of Chile and Venezuela. Drawing on this analysis, the study outlines possible scenarios for the reintegration of both countries, incorporating the perspectives of key stakeholders.